Analisis Pengaruh Lokasi dan Pelayanan Terhadap Minat Masyarakat Menggunakan Pembiayaan BTPN Syariah di Desa Bonan Dolok, Kec. Siabu Kab.Mandailing Natal - Atiroh Mora Mianda (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2024)
ABSTRACT ATIROH MORA MIANDA, NIM. 20150010 Thesis Title "ANALYSIS OF THE EFFECT OF LOCATION AND SERVICE ON PUBLIC INTEREST IN USING BTPN SYARIAH FINANCING (IN BONAN DOLOK VILLAGE, SIABU DISTRICT", Department of Islamic Banking, State Islamic College (STAIN) Madina, 2023. This study aims to determine the effect of Location and Service on Public Interest in Bonan Dolok Village, Siabu District. The development of Islamic Banks continues to increase, according to OJK Islamic Banking Statistics data in 2019, the number of BUS, UUS, and BPRS was 197 units, while in 2023 there were 206 units. Therefore, BTPN Syariah is required to provide the best service so that customers are not disappointed and can compete. The research method used is quantitative research. The population is 100 customers in Bonan Dolok Village, Siabu District. With a sampling technique using the method Random Sampling. Data collection technique by distributing observations and questionnaires. Data analysis technique using t-test, f-test, multiple linear regression, correlation coefficient test and determinant coefficient test. The results of the study indicate that: (1) there is a significant influence of Location on Community Interest with t count 3.973> t table 1.990 and a significant value of 0.001 <0.05. (2) there is a significant influence of Service on Community Interest with t count 4.481> t table 1.990 and a significant value of 0.001 <0.05. Keywords: Location, Service and Village Community Interest